Defect-engineered black indium oxide: A high-performance photothermal material for solar-driven water purification - Tan, Runfa; Shridharan, Tatachari Santhanagopalan; Lee, Jong Ho; Josline, Mukkath Joseph; Lee, Jae Yeong; Bae, Jong Seong; Sivanantham, Arumugam; Jeong, Yoo Jae; Lee, Jae Hyun; Lee, Sangwook; Cho, In Sun (Desalination, 2025)
Defect engineering is a core strategy for controlling the optical, electronic, electrical, and catalytic properties of oxide-based semiconductors. In this study, we used indium oxide as a model system to investigate the impact of point defects on its physicochemical properties and interfacial solar-to-steam generation (ISSG) performance. Our findings revealed that hydrogen incorporation and oxygen vacancy generation can modify the visual color of the material, create deep-level energy states, and significantly enhance sub-bandgap photon absorption. These effects increase the charge carrier concentration, promote non-radiative recombination, and enhance localized heat generation. Additionally, the defects induced high surface energy, which improved surface hydrophilicity. Notably, defect-enriched black In2O3 (b-In2O3) exhibits exceptional photothermal conversion efficiency (74 %) and ISSG performance (evaporation flux: 2.3 kg m−2 h−1) with excellent stability for 60 h under one-sun illumination. We also demonstrated the practical application of b-In₂O₃ in wastewater purification, where the purified water exhibited significantly reduced metal ion concentrations, meeting World Health Organization (WHO) standards. These findings provide valuable insights into the design of oxide-based photothermal materials and emphasize the potential of defect-engineered b-In2O3 as a novel material for efficient solar-driven water purification, thereby offering a sustainable solution for global water scarcity.
Keywords: Deep-level energy state; Deep-levels; Defect engineering; Energy; Indium oxide; Performance; Solar steam; Solar steam generation; Steam generation; Wastewater purification; Deep-level energy states; Defect engineering; In2O3; Solar steam generation; Wastewater purification